PENERAPAN PASAL 310 AYAT (1) DAN (2) JO PASAL 311 AYAT (1) KUHP TENTANG KEJAHATAN MENISTA NAMA BAIK PIHAK KETIGA MELALUI SURAT DALAM AMPLOP TERTUTUP - Imelda Enga Litanti (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT            Deed insult the good name or libel or defame honor someone is an act against the law rejects both orally and in writing to attack the honor of someone who cause damage to a person's reputation or good name and intentionally broadcast to be known by the public interest in accordance with the elements contained in Article 310 of the Criminal Code. Therefore, the act someone who sent a letter in a sealed envelope at all not constitute a libel against third parties who may be charged with Article 310 Paragraph (1) and (2) Jo Article 311 Paragraph (1) of the Criminal Code because it does not meet unsur- elements contained in those chapters. That all actions taken by the Attorney is already true to restore the incomplete file to investigators associated with sufficient evidence used for the prosecution of the case / pemasalahan the author lift.          That the legal consequences arising when not finding sufficient evidence by investigators to mempersangkakan someone has done defamation or libel is Investigators must issue a Letter of Termination of Investigation Case (SP3) and for the defendant / suspect aggrieved complainant can report to the police. Keywords: Law, Criminal, Article 310, Article 311, despised, Honor, Defamation